A high ionic conductivity inorganic sulfide solid-state electrolyte and a preparation method and application thereof
Patent Information
- Application Number
- CN202310981950.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-08-03
AI Technical Summary
然而,硫化物固态电解质的合成几乎难以避免使用成本高昂的Li2S作为原料,极大地限制了硫化物固态电解质的商业化
[0016]本发明得到的高离子电导率无机硫化物固态电解质不仅具有高达0.46mS·cm-1的离子电导率,而且还具有成本优势,以及对金属锂负极良好的相容性。该材料的成本优势来自于合成所需要的原材料:其合成并不需要使用价格昂贵的Li2S,而只需要Li2O、P2S5等常见化合物,因此具有很好的成本效益。与此同时,由于该材料除了Li以外不含其它金属元素,因此被金属锂还原的产物中并不包含具有高电子电导率的金属单质;这些对电子绝缘的还原产物可以很好的阻隔进一步的还原反应,从而使固态电解质实现对金属锂负极良好的相容性。
Smart Images

Figure CN116895831B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of all-solid-state battery materials technology, and in particular to a high-ionic-conductivity inorganic sulfide solid electrolyte, its preparation method, and its application. Background Technology
[0002] All-solid-state batteries, with solid-state electrolytes at their core, hold promise for solving the safety issues and energy density bottlenecks of current commercial lithium-ion batteries, making them a promising next-generation energy storage technology. The key to successfully commercializing all-solid-state batteries lies in finding a suitable solid-state electrolyte. Currently, mainstream solid-state electrolytes are classified into oxide solid-state electrolytes, sulfide solid-state electrolytes, halide solid-state electrolytes, and polymer solid-state electrolytes. Among them, sulfide solid-state electrolytes show great promise due to their higher ionic conductivity and relatively good compatibility with lithium metal anodes. However, the synthesis of sulfide solid-state electrolytes almost inevitably uses expensive Li₂S as a raw material, which greatly limits their commercialization.
[0003] Therefore, developing inorganic sulfide solid electrolytes that are free from dependence on Li2S raw materials and have high ionic conductivity is crucial for promoting the development of sulfide solid electrolytes and even all-solid-state batteries. Summary of the Invention
[0004] The purpose of this invention is to provide an inorganic sulfide solid electrolyte with high ionic conductivity, its preparation method and application, thereby solving the problems existing in the prior art.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0006] This invention provides a high-ionic-conductivity inorganic sulfide solid electrolyte, wherein the general chemical formula of the high-ionic-conductivity inorganic sulfide solid electrolyte is:
[0007] Li a P b S c O d ; among which, 1 <a<12,1<b<6,0<c<15,0<d<15。
[0008] This invention also provides a method for preparing an inorganic sulfide solid electrolyte with high ionic conductivity, comprising the following steps:
[0009] After mixing the raw materials in stoichiometric proportions, ball milling is performed to obtain an inorganic sulfide solid electrolyte with high ionic conductivity.
[0010] Preferably, in the above-mentioned method for preparing an inorganic sulfide solid electrolyte with high ionic conductivity, the raw materials are composed of P2S5 and Li2O.
[0011] Preferably, in the above-mentioned method for preparing an inorganic sulfide solid electrolyte with high ionic conductivity, the ball-to-material ratio of the ball mill is 10-50:1, the ball milling speed is 400-600 rpm, and the ball milling time is 10-50 h.
[0012] Preferably, in the above-mentioned method for preparing an inorganic sulfide solid electrolyte with high ionic conductivity, the ball milling process further includes annealing.
[0013] Preferably, in the above-mentioned method for preparing an inorganic sulfide solid electrolyte with high ionic conductivity, the annealing temperature is 200–400°C and the annealing time is 0.5–5 h.
[0014] This invention also provides an application of a high-ionic-conductivity inorganic sulfide solid electrolyte in all-solid-state batteries.
[0015] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects:
[0016] The high ionic conductivity inorganic sulfide solid electrolyte obtained in this invention not only has a high conductivity of 0.46 mS·cm -1 This material offers excellent ionic conductivity, cost advantages, and good compatibility with lithium metal anodes. The cost advantage stems from the raw materials required for its synthesis: it does not require expensive Li₂S, but only common compounds such as Li₂O and P₂S₅, thus achieving significant cost efficiency. Furthermore, since this material contains no other metal elements besides Li, the products of lithium metal reduction do not contain elemental metals with high electronic conductivity; these electronically insulating reduction products effectively prevent further reduction reactions, thereby ensuring good compatibility of the solid electrolyte with lithium metal anodes. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0018] Figure 1 The uncrystallized Li in Example 1 6.5 P 3.5 S 8.75 O 3.25 Electrochemical impedance spectroscopy;
[0019] Figure 2 The uncrystallized Li7P3S in Example 2 7.5 O 3.5 X-ray diffraction pattern and electrochemical impedance spectroscopy pattern; where a is the X-ray diffraction pattern and b is the electrochemical impedance spectroscopy pattern.
[0020] Figure 3 The uncrystallized Li7P3S in Example 2 7.5 O 3.5 DC polarization spectrum;
[0021] Figure 4 The microcrystalline Li7P3S in Example 2 7.5 O 3.5 X-ray diffraction pattern and electrochemical impedance spectroscopy pattern; where a is the X-ray diffraction pattern and b is the electrochemical impedance spectroscopy pattern.
[0022] Figure 5 The microcrystalline Li7P3S in Example 2 7.5 O 3.5 DC polarization spectrum;
[0023] Figure 6 This is the voltage-time diagram of the symmetrical cell in Example 2;
[0024] Figure 7 The uncrystallized Li in Example 3 7.5 P 2.5 S 6.25 O 3.75 Electrochemical impedance spectroscopy;
[0025] Figure 8 Microcrystalline Li in Example 3 7.5 P 2.5 S 6.25 O 3.75 X-ray diffraction pattern and electrochemical impedance spectroscopy pattern; where a is the X-ray diffraction pattern and b is the electrochemical impedance spectroscopy pattern.
[0026] Figure 9 This is the voltage-time diagram of the symmetrical cell in Example 3;
[0027] Figure 10 The electrochemical impedance spectroscopy of uncrystallized Li8P2S5O4 in Example 4 is shown.
[0028] Figure 11 The images show the X-ray diffraction pattern and electrochemical impedance spectroscopy of microcrystalline Li8P2S5O4 in Example 4; where a is the X-ray diffraction pattern and b is the electrochemical impedance spectroscopy.
[0029] Figure 12 This is the voltage-time diagram of the symmetrical cell in Example 4;
[0030] Figure 13 The uncrystallized Li in Example 5 8.5 P 1.5 S 3.75 O 4.25electrochemical impedance spectroscopy plot. Detailed Description of the Embodiments
[0031] The present invention provides an inorganic sulfide solid electrolyte with high ionic conductivity, and the chemical general formula of the inorganic sulfide solid electrolyte with high ionic conductivity is:
[0032] Li a P b S c O d ;
[0033] wherein, a is preferably 1<a<12, more preferably 4<a<10, and even more preferably 6<a<8;
[0034] b is preferably 1<b<6, more preferably 2<b<5, and even more preferably 2<b<4;
[0035] c is preferably 0<c<15, more preferably 3<c<12, and even more preferably 5<c<8;
[0036] d is preferably 0<d<15, more preferably 0<d<9, and even more preferably 0<d<5.
[0037] The present invention further provides a preparation method of the inorganic sulfide solid electrolyte with high ionic conductivity, comprising the following steps:
[0038] Raw materials in a stoichiometric ratio are mixed and then subjected to ball milling, to obtain the inorganic sulfide solid electrolyte with high ionic conductivity.
[0039] In the present invention, the raw materials are preferably composed of P2S5 and Li2O.
[0040] In the present invention, the ball-to-material ratio of the ball milling is preferably 10 to 50:1, more preferably 14 to 45:1, and even more preferably 20 to 30:1; the rotational speed of the ball milling is preferably 400 to 600 rpm, more preferably 420 to 550 rpm, and even more preferably 460 to 500 rpm; the duration of the ball milling is preferably 10 to 50 h, more preferably 15 to 42 h, and even more preferably 20 to 30 h.
[0041] In the present invention, after the ball milling, an annealing treatment is further included, and the number of times of the annealing treatment is preferably 1 to 2 times, more preferably 1 time.
[0042] In the present invention, the material after the annealing treatment is a microcrystalline material, and the material without the annealing treatment is an uncrystallized material.
[0043] In this invention, the annealing temperature is preferably 200-400°C, more preferably 230-360°C, and even more preferably 270-330°C; the annealing time is preferably 0.5-5 hours, more preferably 1-4 hours, and even more preferably 2.5-3 hours.
[0044] This invention also provides an application of a high-ionic-conductivity inorganic sulfide solid electrolyte in all-solid-state batteries.
[0045] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0046] Example 1
[0047] A high ionic conductivity inorganic sulfide solid electrolyte Li 6.5 P 3.5 S 8.75 O 3.25 The preparation method includes the following steps:
[0048] In an argon-protected glove box (water and oxygen content less than 0.01 ppm), P2S5 and Li2O were weighed according to stoichiometric ratio and placed in a 125 mL zirconia ball mill jar (ball-to-material ratio 15:1, zirconia grinding balls with a diameter of 5 mm). After sealing, the jar was ball-milled at 500 rpm for 20 h in a BM6 pro high-energy ball mill from Greedmann Corporation in China to obtain uncrystallized Li. 6.5 P 3.5 S 8.75 O 3.25 Its electrochemical impedance spectroscopy is as follows Figure 1 As shown. By Figure 1 It can be seen that the uncrystallized Li 6.5 P 3.5 S 8.75 O 3.25 The room temperature ionic conductivity is 9.98 × 10⁻⁶. -6 S / cm. The ionic conductivity was measured after the solid electrolyte material was simply cold-pressed into sheets at 300 MPa, indicating that Li... 6.5 P 3.5 S 8.75 O 3.25 It has good deformation capacity.
[0049] Example 2
[0050] A high ionic conductivity inorganic sulfide solid electrolyte Li7P3S 7.5 O 3.5The preparation method includes the following steps:
[0051] In an argon-protected glove box (water and oxygen content less than 0.01 ppm), P2S5 and Li2O were weighed according to stoichiometric ratio and placed in a 125 mL zirconia ball mill jar (ball-to-material ratio of 15:1, zirconia grinding balls with a diameter of 5 mm). After sealing, the jar was ball-milled at 500 rpm for 10 h in a BM6 pro high-energy ball mill from Greedmann Corporation in China to obtain amorphous Li7P3S. 7.5 O 3.5 ; Uncrystallized Li7P3S 7.5 O 3.5 The sample was sealed in a quartz tube and subjected to two annealing stages at 270℃ and 290℃, with annealing times of 0.5 h and 1 h, respectively, to obtain microcrystalline Li7P3S. 7.5 O 3.5 .
[0052] Uncrystallized Li7P3S 7.5 O 3.5 and microcrystalline Li7P3S 7.5 O 3.5 The X-ray diffraction pattern, electrochemical impedance spectroscopy, and DC polarization pattern are as follows: Figures 2-5 As shown. By Figures 2-5 It can be seen that the uncrystallized Li7P3S 7.5 O 3.5 The room temperature ionic conductivity is 2.92 × 10⁻⁶. -5 S / cm, room temperature electronic conductivity (σ) e The value is 8.73 × 10 -8 S / cm; Microcrystalline Li7P3S 7.5 O 3.5 The room temperature ionic conductivity is 4.56 × 10⁻⁶. -4 S / cm, room temperature electronic conductivity (σ) e The value is 9.76 × 10 -9 S / cm. Ionic and electronic conductivity were measured after simply cold-pressing the solid electrolyte material into sheets, indicating that Li7P3S... 7.5 O 3.5 The fact that Li7P3S exhibits excellent deformation ability and that its ionic conductivity is four orders of magnitude higher than its electronic conductivity proves its superior properties. 7.5 O 3.5 It is a pure ionic conductor that can be used as a solid electrolyte.
[0053] The symmetric cell was assembled in an argon-protected glove box (water and oxygen content less than 0.01 ppm). The specific process is as follows:
[0054] First, 120 mg of Li7P3S was injected into a 10 mm diameter PEEK mold under a pressure of 1.2 tons.7.5 O 3.5 Powder is pressed into shape and held under pressure for 2 minutes; subsequently, lithium sheets with a diameter of 10 mm are lightly pressed and attached to Li7P3S. 7.5 O 3.5 Both sides of the plate. Finally, an external pressure of less than 10 kg is applied to the entire battery. The voltage-time diagram of this symmetrical battery is shown below. Figure 6 As shown, by Figure 6 It can be seen that this symmetrical cell is at 0.1 mA·cm -2 The overpotential stabilizes at around 50mV during cycling at a current density, and the solid electrolyte can cycle stably for at least 4500 hours, indicating that the solid electrolyte and lithium metal have good compatibility.
[0055] Example 3
[0056] A high ionic conductivity inorganic sulfide solid electrolyte Li 7.5 P 2.5 S 6.25 O 3.75 The preparation method includes the following steps:
[0057] In an argon-protected glove box (water and oxygen content less than 0.01 ppm), P2S5 and Li2O were weighed according to stoichiometric ratio and placed in a 125 mL zirconia ball mill jar (ball-to-material ratio 15:1, zirconia grinding balls with a diameter of 5 mm). After sealing, the jar was ball-milled at 500 rpm for 10 h in a BM6 pro high-energy ball mill from Greedmann Corporation in China to obtain uncrystallized Li. 7.5 P 2.5 S 6.25 O 3.75 ; Uncrystallized Li 7.5 P 2.5 S 6.25 O 3.75 The microcrystalline Li was obtained by sealing it in a quartz tube and annealing it at 275°C for 3 hours. 7.5 P 2.5 S 6.25 O 3.75 .
[0058] Uncrystallized Li 7.5 P 2.5 S 6.25 O 3.75 Electrochemical impedance spectroscopy and microcrystalline Li 7.5 P 2.5 S 6.25 O 3.75 The X-ray diffraction pattern and electrochemical impedance spectroscopy are as follows: Figures 7-8 As shown. By Figures 7-8 It can be seen that the uncrystallized Li 7.5 P 2.5 S 6.25O 3.75 The room temperature ionic conductivity is 2.35 × 10⁻⁶. -5 S / cm, microcrystalline Li 7.5 P 2.5 S 6.25 O 3.75 The room temperature ionic conductivity is 6.56 × 10⁻⁶. - 5 S / cm. The ionic conductivity is measured after the solid electrolyte material is simply cold-pressed into a sheet, indicating that Li... 7.5 P 2.5 S 6.25 O 3.75 It has good deformation capacity.
[0059] The symmetric cell was assembled in an argon-protected glove box (water and oxygen content less than 0.01 ppm). The specific process is as follows:
[0060] First, 120 mg of Li was injected into a 10 mm diameter PEEK mold under a pressure of 1.2 tons. 7.5 P 2.5 S 6.25 O 3.75 Powder is pressed into shape and held under pressure for 2 minutes; then, lithium sheets with a diameter of 10mm are lightly pressed and attached to the Li... 7.5 P 2.5 S 6.25 O 3.75 Both sides of the plate. Finally, an external pressure of less than 10 kg is applied to the entire battery. The voltage-time diagram of this symmetrical battery is shown below. Figure 9 As shown, by Figure 9 It can be seen that this symmetrical cell is at 0.1 mA·cm -2 The overpotential stabilizes at around 50mV during cycling at a given current density, and the system can cycle stably for at least 100 hours, indicating that the solid electrolyte and lithium metal have good compatibility.
[0061] Example 4
[0062] A method for preparing a high-ionic-conductivity inorganic sulfide solid electrolyte Li8P2S5O4 includes the following steps:
[0063] In an argon-protected glove box (water and oxygen content less than 0.01 ppm), P2S5 and Li2O were weighed according to the stoichiometric ratio and placed in a 125 mL zirconia ball mill jar (ball-to-material ratio of 15:1, zirconia grinding ball diameter of 5 mm). After sealing, the jar was ball-milled at 500 rpm for 10 h in a high-energy ball mill BM6 pro of Greedmann Corporation in China to obtain amorphous Li8P2S5O4. The amorphous Li8P2S5O4 was then sealed in a quartz tube and annealed at 265 °C for 0.5 h to obtain microcrystalline Li8P2S5O4.
[0064] The electrochemical impedance spectroscopy (EIS) of uncrystalline Li8P2S5O4 and the X-ray diffraction (XRD) and electrochemical impedance spectroscopy (EIS) of microcrystalline Li8P2S5O4 are shown below. Figures 10-11 As shown. By Figures 10-11 It can be seen that the room temperature ionic conductivity of uncrystallized Li8P2S5O4 is 2.70 × 10⁻⁶. -5 The room-temperature ionic conductivity of microcrystalline Li8P2S5O4 is 3.32 × 10⁻⁶ S / cm. -5 S / cm. The ionic conductivity was measured after the solid electrolyte material was simply cold-pressed into sheets, indicating that Li8P2S5O4 has good deformation capability.
[0065] The symmetric cell was assembled in an argon-protected glove box (water and oxygen content less than 0.01 ppm). The specific process is as follows:
[0066] First, 120 mg of Li8P2S5O4 powder was pressed into shape in a 10 mm diameter PEEK mold under a pressure of 1.2 tons and held at that pressure for 2 minutes. Then, 10 mm diameter lithium sheets were gently pressed and attached to both sides of the Li8P2S5O4 sheet. Finally, an external pressure of less than 10 kg was applied to the entire battery. The voltage-time graph of this symmetrical battery is shown below. Figure 12 As shown, by Figure 12 It can be seen that this symmetrical cell is at 0.1 mA·cm -2 The overpotential stabilizes at around 150mV during cycling at a current density, and the solid electrolyte can cycle stably for at least 100 hours, indicating that the solid electrolyte and lithium metal have good compatibility.
[0067] Example 5
[0068] A high ionic conductivity inorganic sulfide solid electrolyte Li 8.5 P 1.5 S 3.75 O 4.25 The preparation method includes the following steps:
[0069] In an argon-protected glove box (water and oxygen content less than 0.01 ppm), P2S5 and Li2O were weighed according to stoichiometric ratio and placed in a 125 mL zirconia ball mill jar (ball-to-material ratio 15:1, zirconia grinding balls with a diameter of 5 mm). After sealing, the jar was ball-milled at 500 rpm for 10 h in a BM6 pro high-energy ball mill from Greedmann Corporation in China to obtain uncrystallized Li. 8.5 P 1.5 S 3.75 O 4.25 .
[0070] Uncrystallized Li 8.5 P 1.5 S 3.75 O4.25 The electrochemical impedance spectroscopy is as follows Figure 13 As shown. By Figure 13 It can be seen that the uncrystallized Li 8.5 P 1.5 S 3.75 O 4.25 The room temperature ionic conductivity is 6.97 × 10⁻⁶. -6 S / cm. The ionic conductivity was measured by simply cold-pressing solid electrolyte material powder into sheets, indicating that Li... 8.5 P 1.5 S 3.75 O 4.25 It has good deformation capacity.
[0071] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a high-ionic-conductivity inorganic sulfide solid electrolyte, characterized in that, Includes the following steps: After mixing the raw materials in stoichiometric proportions, ball milling is performed to obtain an inorganic sulfide solid electrolyte with high ionic conductivity. The raw material is composed of P2S5 and Li2O; The general chemical formula of the high ionic conductivity inorganic sulfide solid electrolyte is: Li a P b S c O d ; among which, 1 <a<12,1<b<6,0<c<15,0<d<15。 2. The method for preparing a high ionic conductivity inorganic sulfide solid electrolyte according to claim 1, characterized in that, The ball-to-material ratio of the ball mill is 10~50:1, the rotation speed of the ball mill is 400~600 rpm, and the milling time is 10~50 h.
3. The method for preparing a high ionic conductivity inorganic sulfide solid electrolyte according to claim 2, characterized in that, The ball milling process also includes annealing.
4. The method for preparing a high ionic conductivity inorganic sulfide solid electrolyte according to claim 3, characterized in that, The annealing temperature is 200~400℃, and the annealing time is 0.5~5h.
5. The high ionic conductivity inorganic sulfide solid electrolyte prepared by the method of any one of claims 1 to 4.
6. The application of the high ionic conductivity inorganic sulfide solid electrolyte as described in claim 5 in all-solid-state batteries.
Citation Information
Patent Citations
Sulfide solid electrolytes, preparation method thereof and all-solid lithium secondary battery
CN103531841A